2018
DOI: 10.1521/aeap.2018.30.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Sexual and Reproductive Health Protective and Risk Factors of Batswana Adolescents: Implications for Parent and Adolescent Interventions

Abstract: Adolescents in sub-Saharan Africa and in Botswana in particular continue to bear the brunt of the HIV epidemic. This analysis assessed gender differences among theory-based sexual and reproductive health protective and risk factors in a cross-sectional sample of 228 Batswana adolescents. Incongruence between preferred and actual sources of sexual information and several important gender differences in parent-adolescent relationships, psychosocial influences, and adolescent sexual behaviors were identified. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Absalon et al, (2006) compared sexual behaviours and determined sexual risk correlates associated with HIV by gender among street-recruited drug users and found that men reported higher-risk sexual behaviours as compared to women. Looking at these differences, Sun et al, (2018) suggest that interventions should address gender differences and consider offering parallel interventions.…”
Section: Gender and Hivmentioning
confidence: 99%
“…Absalon et al, (2006) compared sexual behaviours and determined sexual risk correlates associated with HIV by gender among street-recruited drug users and found that men reported higher-risk sexual behaviours as compared to women. Looking at these differences, Sun et al, (2018) suggest that interventions should address gender differences and consider offering parallel interventions.…”
Section: Gender and Hivmentioning
confidence: 99%
“…Despite its huge potential benefits for adolescent health outcomes and public health in general, gender-related issues may limit the impact of health literacy. Gender is a critical determinant of health that intersects with many aspects of health and has the potential to exacerbate existing health inequities (Sun et al, 2018). Shakya et al (2019) explained that gender factors could have a disproportionate effect on teenagers' health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The attitudinal gender differences of the young female population with regard to transactional sex are thought to result in risky behaviours such as unprotected sex with older men. 17 Although it is known that the young female population is more susceptible to HIV and AIDS infection, there is a paucity of research on gender differences in knowledge, attitudes and behaviours among young people in higher education settings, thereby inhibiting an in-depth understanding of factors contributing to HIV and AIDS infection among this population in South Africa. Such a gap in the literature negatively influences policy and practice aimed at reducing HIV and AIDS rates among vulnerable youth within this context.…”
Section: Introductionmentioning
confidence: 99%